Gallery One at the Cleveland Museum of Art. (July 2014) - Alexander, Jane
Abstract How can art museums use interpretive technology to engage visitors actively in new kinds of experiences with works of art? What are the best strategies for integrating technology into the visitor experience? In 2012, the Cleveland Museum of Art responded with Gallery One, an interactive art gallery that opened to stakeholders on December 12, and went through a six‐week testing period before its public opening on January 21, 2013. Gallery One drew from extensive audience research and was part of a major building and renovation project in which CMA reinstalled and reinterpreted the entire permanent collection in new and renovated gallery spaces. The end result was an innovative and robust blend of art, technology, design, and a unique user experience that emerged through the collaboration of staff across the museum and with outside consultants.